How do Twitter users feel about telehealth? A mixed‐methods analysis of experiences, perceptions and expectations - Hannah Sazon; Soraia de Camargo Catapan; Afshin Rahimi; Oliver J. Canfell; Jaimon Kelly (Health Expectations)
Abstract Background Telehealth use has increased considerably in the last years and evidence suggests an overall positive sentiment towards telehealth. Twitter has a wide userbase and can enrich our understanding of telehealth use by users expressing their personal opinions in an unprompted way. This study aimed to explore Twitter users' experiences, perceptions and expectations about telehealth over the last 5 years. Methods Mixed‐methods study with sequential complementary quantitative and qualitative phases was used for analysis stages comprising (1) a quantitative semiautomated analysis and (2) a qualitative research‐led thematic analysis. A machine learning model was used to establish the data set with relevant English language tweets from 1 September 2017 to 1 September 2022 relating to telehealth using predefined search words. Results were integrated at the end. Results From the initial 237,671 downloaded tweets, 6469 had a relevancy score above 0.8 and were input into Leximancer and 595 were manually analysed. Experiences, perceptions and expectations were categorised into three domains: experience with telehealth consultation, telehealth changes over time and the purpose of the appointment. The most tweeted experience was expectations for telehealth consultation in comparison to in‐person consultations. Users mostly mentioned the hope that waiting times for the consultations to start to be less than in‐person, more telehealth appointments to be available and telehealth to be cheaper. Perceptions around the use of telehealth in relation to healthcare delivery changes brought about by the COVID‐19 pandemic were also expressed. General practitioners were mentioned six times more than other healthcare professionals. Conclusion/Implications This study found that Twitter users expect telehealth services to be better, more affordable and more available than in‐person consultations. Users acknowledged the convenience of not having to travel for appointments and the challenges to adapt to telehealth. Patient or Public Contribution An open data set with 237,671 tweets expressing users' opinions in an unprompted way was used as a source for telehealth service users, caregivers and members of the public experiences, perceptions and expectations of telehealth.